Behavior driven development framework and strategy for a product development group - Cruz, Alfa F.
Behavior Driven Development (BDD) is an Agile software development method that focuses on the behavior of the feature from the perspective of all of its stakeholders. It is about developing and delivering better software that offers real value to its users and to the business. It encourages everyone to communicate and collaborate to be able to clearly identify the requirements or the business need through specifications by example. BDD helps the team to focus more on identifying, understanding and developing valuable features that will result as a software that matters. Also, it aims that all features be implemented just as planned to be able to catch up with the market timings.